Analisis Perlindungan Hukum bagi Para Pihak dalam Kontrak Jual Beli Listrik di Indonesia - , Rita Kristiyani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to study the regulation on power purchase in Indonesia, how this regulation is implemented, and how effective this regulation gives protection to the all participants. Besides this research aims to identify the opinion of investors on law protections aspect for investors as well as the position of all the participants in for PPA in Indonesia. This research used two approach: 1) juridical research, through literature and secondary data review, 2) juridical empirical, through study on implementation of normative law. Secondary data are collected, examine, and evaluated from various references related to the topic of the research. Primary data are obtain from electronic mails and interview using interview guidelines. The results are analyzed using several law approaches that are presented descriptively and qualitatively. The results are:1) regulations on PPA in Indonesia, 2) Implementation of the regulation and the effectiveness of the regulation to protect all the participants, 3) the opinion of the investors on the law protections aspect for the investors as well as the position of all the participants on PPA in Indonesia.